PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR PADA SEKTOR INDUSTRI PERTAMBANGAN - Arta Dessy (Business Accounting Review, 2015)
This study was conducted to know the effect of Corporate Social Responsibility (CSR) on the response of investors. Some inconsistency in the results of previous studies either in a multi industry and mining industry in Indonesia was a motivation to prove the influence of CSR on the response of investors.CSRwas measured byusingindicatorsofthe Global ReportingIndex(GRI) version3.1. whereastomeasure the responseof investorsusingthe CumulativeAbnormal Return(CAR). Control variablesusedin this studywere the Returnon Assets(ROA), firm size, Debtto Equity Ratio(DER), andmarket share. This research was conductedatthe companiesinthe miningindustrysectorsthat listedinIndonesia Stock Exchange(IDX) in2008-2012with a sample of123 firm-year.The resultsofthe t testinthe miningindustrysectorshowedthatCSRhad asignificantand positiveaffecton the response ofinvestors. The control variablesof firm sizeandmarket share hadsignificant and positive influenceoninvestorresponse. Whilethe resultsforthe controlvariablesROAandDERdid notaffect theresponseof investors. Based on theF test resultsshowedCSR, ROA, firm size, DER, and themarket sharehadsignificant influenceto investorresponse.